Forced responses analysis of a rotor system with squeeze film damper during flight maneuvers using finite element method. (April 2018) - Han, Bingbing; Ding, Qian
Highlights: Finite element rotor model and the corresponding hybrid numerical method are employed. The damping effect of squeeze film damper is found enhanced by maneuvering flight. Characteristics of transient response during flight maneuvers are investigated. Sub- and super-harmonic resonance phenomena are found induced by maneuvers. The influence of center spring on damping effect of SFD is studied. Abstract: The rotor system of aero engine will endure a severe bad working condition when aircrafts do flight maneuvers. This process can result in Multi-period or irregular transient vibration. In this paper a rotor/ball bearing system model is first established by using the finite element method. The dynamic characteristics of the system during maneuvers, with linear damping supports and squeeze film damper supports at the shaft ends respectively, are subsequently studied by adopting a corresponding hybrid numerical method. Time histories of velocity and displacement are employed to analyze the transient response during maneuvers. Frequency/waterfall spectra are used to reveal the sub- and super resonance in flight maneuvers. The results indicate that transient responses can be induced by both the commencement and the termination of the maneuvers. The squeeze film dampers (SFD) perform effectively on suppressing the amplitude of transient responses. Its damping effect is enhanced by flight maneuvers. The stiffness of central spring structure is found playing an important role on the damping behavior of SFD. Sub- and super-harmonic resonances can happen during flight maneuvers for linear damping supports but be suppressed significantly by the SFD.